LARGE DEFORMATIONS OF THIN RING PLATE. II - Nazaryan, E. A.; Arakelyan, M. M.; Markosyan, A. S.; Arab, N. N. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
The basic opportunity of the decision of tasks final forming is shown at plain stress condition in view of interconnected change thickness and hardening deformation parameter. For opposite sign and similar sing conditions the sizes of plastic area and distribution component of deformations are determined.
Keywords: thin ring plates; large plastic deformations; speeds of radial stress; thickness of the material